Man, Play and Games - Caillois, Roger (Chicago, IL University of Illinois Press, 2001)
According to Roger Caillois, play is "an occasion of pure waste: waste of time, energy, ingenuity, skill, and often of money." In spite of this--or because of it--play constitutes an essential element of human social and spiritual development.In this classic study, Caillois defines play as a free and voluntary activity that occurs in a pure space, isolated and protected from the rest of life. Play is uncertain, since the outcome may not be foreseen, and it is governed by rules that provide a level playing field for all participants. In its most basic form, play consists of finding a response to the opponent's action--or to the play situation--that is free within the limits set by the rules.Caillois qualifies types of games-- according to whether competition, chance, simulation, or vertigo (being physically out of control) is dominant--and ways of playing, ranging from the unrestricted improvisation characteristic of children's play to the disciplined pursuit of solutions to gratuitously difficult puzzles. Caillois also examines the means by which games become part of daily life and ultimately contribute to various cultures their most characteristic customs and institutions.Presented here in Meyer Barash's superb English translation, Man, Play and Games is a companion volume to Caillois's Man and the Sacred."Well worth the attention of every sociologist interested in the relationship of culture to play."--American Sociological Review "A book to be read for ideas."--American Journal of Sociology "An excellently conceived work."--Social ForcesRoger Caillois (1913-78), a French philosopher and writer, was a cofounder of France's pathbreaking Collège de Sociologie pour l'Étude du Sacré and the founding editor of Diogenes, the journal of the International Council for Philosophy and Humanistic Studies. His books included works of anthropology, sociology, psychoanalysis, art, and literary criticism. Meyer Barash, coeditor of Marriage and the Family: A Comparative Analysis of Contemporary Problems, was on the faculty of Hofstra College in New York.
Keywords: Philosophy; Game